2008
DOI: 10.1007/s11577-008-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Arbeitsteilung, Berufsorientierung und Partnerschaftsstabilität – Ehen und nichteheliche Lebensgemeinschaften im Vergleich*

Abstract: Zusammenfassung: Das zentrale Ergebnis der Arbeit ist, dass sich Ehen und nicht eheliche Lebensgemeinschaften im Hinblick auf den Zusammenhang zwischen der außerhäuslichen Arbeitsteilung und der Partnerschaftsstabilität unterscheiden. Ehen werden durch die Erwerbsbeteiligung der Frau destabilisiert und durch eine traditio nelle Arbeitsteilung stabilisiert. Empirisch äußert sich dies in einem positiven Effekt des Einkommens bzw. der Berufsorientierung der Frau und einem negativen Effekt des relativen Einkommens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
6
1
2
Order By: Relevance
“…We furthermore found that men in non-marital unions seemed to be more likely to be on leave than fathers in marital unions. This contradicts prior research for Scandinavian countries (Sundström and Duvander 2002), but it is in line with findings for Germany, which showed that the division of housework is more equal in non-marital than in marital unions (Lois 2008).…”
Section: Resultscontrasting
confidence: 74%
“…We furthermore found that men in non-marital unions seemed to be more likely to be on leave than fathers in marital unions. This contradicts prior research for Scandinavian countries (Sundström and Duvander 2002), but it is in line with findings for Germany, which showed that the division of housework is more equal in non-marital than in marital unions (Lois 2008).…”
Section: Resultscontrasting
confidence: 74%
“…For example, gender attitudes could be more equal in non-marital than in marital unions. There is some empirical evidence supporting this assumption which shows that non-marital couples share housework more equally than married couples (Lois 2008;Wengler et al 2008). However, it has also been proposed that marriage may represent a stronger commitment than cohabitation, which is why married fathers want to invest more in their children than non-marital fathers (Sundström and Duvander 2002;Lappegard 2008;Naz 2007).…”
Section: Hypotheses Regarding the Determinants Of Men's Parental Leavmentioning
confidence: 99%
“…Additionally, due to the small number of cases, it was not possible to consider differences between various subgroups that might be important, such as differences between men and women or between marriages, cohabitations and dating relationships. This is particularly problematic when analysing the effect of employment status on relationship stability, because previous research reported different effects between men and women and between marriages and non-marital cohabitations (Lois 2008).…”
Section: Discussionmentioning
confidence: 99%
“…When not only considering married couples, the establishment of a common household and marriage itself can also be seen as investments in relationship-specifi c capital. Previous studies showed that marriages are more stable than non-marital cohabitations and much more stable than dating relationships (Asendorpf 2008;Boyle et al 2008;Kalmijn et al 2007;Lois 2008).…”
Section: Further Determinants Of Divorce and Separationmentioning
confidence: 99%